SOCIAL PHOBIA: TREATMENT IN GROUP OF THE FEAR OF SPEAKING IN PUBLIC IN FOUR SUBJECTS THROUGH A DESIGN N=1 - Maciá Antón, Diego; García López, Luis Joaquín (Anales de Psicología / Annals of Psychology)
Social phobia is a rescently defined disorder of which, so far, little is known in relation its origin and treatment, and of which the fear of speaking in public is considered to be a specific form of social phobia.The reason for the presentation of this work is to explain the results of a cognitive-conductual treatment, usin techniques of exposition, discussion of thoughts, respiratory training in self-instruction and bibliotherapy through four designs of a simple subject (n=1) and in a group therapy.The results are encouraging and provide data over the importance of the cognitive techniques, at least in thuis disorder (the importance of the fear of negative evaluation), leading to the modification the structure of the sessions and improving others disorders (a case of writer cramp).